Evaluating the anxiety and depression status of prostate cancer patients whose operations were postponed because of the COVID‐19 pandemic. Issue 8 (26th May 2021) - Kizilkan, Yalcin; Senel, Samet; Ozercan, Ali Yasin; Balci, Melih; Eroglu, Unsal; Aktas, Binhan Kagan; Bulut, Suleyman; Ozden, Cuneyt; Tuncel, Altug
Abstract: Aim: In this study, we aimed to evaluate the anxiety and depression status of prostate cancer (PCa) patients whose planned operations in the urology clinic of our hospital, which is serving as a pandemic hospital in Turkey have been postponed because of the coronavirus disease 2019 pandemic. Methods: This survey study was conducted at urology clinic of Ankara City Hospital between March 1 and June 1, 2020, and included 24 male patients who agreed to answer the questionnaires (State‐Trait Anxiety Inventory [STAI] I and II and Beck Depression Inventory [BDI]). Demographical and clinical data (age, time since diagnosis, total serum prostate‐specific antigen (PSA) levels, risk groups according to the D'Amico classification system, smoking, alcohol habitus, major surgical history and comorbidities) of the patients were collected from hospital software. Results: The mean STAI‐I score of the patients (46.7 ± 1.4 [44‐49]) was significantly higher than their STAI‐II score (41.7 ± 2.4 [39‐47]) ( P  < .001). The negative correlation between the decrease in age and STAI‐I score was found to be statistically significant ( r  = 0.439, P  < .05). The mean BDI score of the patients was 4.3 ± 3.2 (0‐13), which was compatible with mild depression. There was no statistically significant difference among the time elapsed from diagnosis, PSA levels, smoking and alcohol habitus, major surgical history and comorbidity status and STAI‐I, STAI‐II and BDI scores ( P  > .05). Conclusion: Prostate cancer patients with postponed operations should be guided properly in order to manage their anxiety status especially young patients.